EFEKTIVITAS KONSELING KELOMPOK TEKNIK COGNITIVE DEFUSION UNTUK MENINGKATKAN SELF EFFICACY SISWA SMA - Emiliah Emiliah; Syska Purnama Sari; Arizona Arizona (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Students' ability to cope with academic demands is strongly influenced by their self-efficacy, as confidence in one's own capabilities shapes the willingness to face challenges, sustain effort, and accomplish academic tasks. When this belief is weak, students are more likely to avoid challenging situations, experience diminished learning motivation, and give up easily when confronted with difficulties. This condition highlights the need for group counseling interventions incorporating the cognitive defusion technique to help students develop a more adaptive relationship with their negative thoughts. The effectiveness of this intervention was examined using a quantitative approach with a pre-experimental One Group Pretest–Posttest design. The study involved six students purposively selected from a population of 70 eleventh-grade students from classes XI B1 and XI C1 at SMA Negeri 7 Palembang based on observation results, pretest scores, and recommendations from the school counselor. Data were collected through a self-efficacy questionnaire and documentation, and subsequently analyzed using the Wilcoxon Signed-Rank Test. The findings revealed a significant improvement in students' self-efficacy following the intervention, with a significance value of 0.028 (p < 0.05). These results indicate that the cognitive defusion technique is an effective group counseling strategy for strengthening students' self-efficacy while providing additional empirical support for the implementation of the Acceptance and Commitment Therapy (ACT) approach in school guidance and counseling services. ABSTRAK Kemampuan siswa untuk menghadapi tuntutan akademik sangat dipengaruhi oleh self-efficacy, karena keyakinan terhadap kemampuan diri menentukan keberanian dalam menghadapi tantangan, mempertahankan usaha, dan menyelesaikan tugas. Ketika keyakinan tersebut rendah, siswa cenderung menghindari situasi yang menantang, kehilangan motivasi, serta mudah menyerah saat menemui hambatan. Kondisi tersebut mendorong penerapan layanan konseling kelompok yang memanfaatkan teknik cognitive defusion sebagai strategi untuk membantu siswa membangun hubungan yang lebih adaptif terhadap pikiran-pikiran negatif. Efektivitas intervensi tersebut dikaji melalui penelitian kuantitatif dengan desain pre-experimental One Group Pretest–Posttest. Penelitian melibatkan enam siswa yang dipilih secara purposive dari populasi 70 siswa kelas XI B1 dan XI C1 SMA Negeri 7 Palembang berdasarkan hasil observasi, pretest, dan rekomendasi guru bimbingan dan konseling. Pengumpulan data dilakukan menggunakan angket self-efficacy dan dokumentasi, kemudian dianalisis dengan Uji Wilcoxon Signed Rank. Hasil analisis menunjukkan adanya peningkatan self-efficacy setelah intervensi dengan nilai signifikansi 0,028 (p < 0,05). Temuan ini mengindikasikan bahwa teknik cognitive defusion efektif diterapkan dalam layanan konseling kelompok untuk memperkuat self-efficacy siswa, sekaligus memberikan dukungan empiris terhadap implementasi pendekatan Acceptance and Commitment Therapy (ACT) dalam praktik bimbingan dan konseling di sekolah.